HUBUNGAN PENGETAHUAN SIKAP DAN KONDISI LINGKUNGAN DENGAN PERSONAL HYGIENE ORANGTUA BADUTA STUNTING DI WILAYAH KERJA PUSKESMAS I CILONGOK KABUPATEN BANYUMAS - Elviera Gamelia; Ara Amalia; Siti Masfiah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Background: Personal Hygiene one of the factors that cause children to be exposed to infectious diseases, causing stunting in children. Poor personal hygiene can cause loss of essential nutrients in the growth of toddlers. This study aims to determine the relationship between knowledge, attitudes and environmental conditions with the personal hygiene of parents of stunting children. Methodology: This research using a cross sectional approach with observational analytical study design. The population of 1,722 respondents and a sample of 112 parents used a purposive sampling technique with inclusion and exclusion criteria. Data analysis in 3 stages, univariate analysis, bivariate analysis (Chi-Square), and multivariate analysis (Logistics Regression). Research result: A total of 62 respondents (55.4%) had a SLTP/MTs education, and 104 respondents (92.9%) did not work. There is a relationship between knowledge (p = 0.003) and attitude (p = 0.008) with personal hygiene. The results of multivariate analysis showed that the most influential variable was knowledge (p =0.009, OR = 2.985) on the personal hygiene of parents of stunting children under two. Conclusion: There is an influence of knowledge and attitudes on the personal hygiene of parents of stunting children. Parents can improve and teach personal hygiene to children to prevent stunting.